Group-Based Trajectory Analysis of Emotional Symptoms among Survivors after Severe Traumatic Brain Injury - Ren, Dianxu (J Head Trauma Rehabil, 2017)
OBJECTIVES: Depressive symptoms and anxiety are fairly common emotional outcomes after severe TBI. Life satisfaction is a main factor in the general construct of subjective well-being. However, there is limited literature available on the interrelationship between emotional outcomes and life satisfaction post-severe TBI over time. The purpose of this study was to characterize distinct patterns of change in depressive symptoms, anxiety and life satisfaction over 24 months after severe TBI and evaluate the interrelationship of different trajectory groups among them as well as associated subject characteristics. METHODS: This prospective study used longitudinal data collected from the University of Pittsburgh Brain Trauma Research Center (BTRC) from survivors of severe TBI (N=129). In addition to demographic and injury related data, depressive symptoms, anxiety and life satisfaction were collected at 3, 6, 12, and 24 months post-injury. A group-based trajectory model was performed to identify distinct longitudinal patterns of depressive symptoms, anxiety and life satisfaction. The interrelationships of distinct trajectory groups were examined using chi-square tests. A multivariate logistic regression model was used to examine the predictors of different emotional symptom trajectories. RESULTS: The group-based trajectory model identified 2 distinct patterns of each of 3 outcomes: constantly low and constantly high depressive symptoms group (70.4% vs 29.6%), constantly low and constantly high anxiety group (69.1% vs 30.9%) and low-decreasing and high-stable life satisfaction groups (56.3% vs 43.7%) A strong pair-wise association was observed between trajectory group membership for depressive symptoms and anxiety (p<0.0001), depressive symptoms and life satisfaction (p<0.0001), anxiety and life satisfaction (p<0.001). Subjects with increased severe injury were more likely to belong to the high-stable depressive symptoms group, while there were no significant associations between age, gender, race, education, marriage status and distinct depressive symptoms, anxiety, and life satisfaction trajectory groups. CONCLUSIONS: A group-based trajectory model revealed patterns of emotional symptoms that have not been fully explored among survivors of severe TBI. There appear to be distinct trajectory patterns for depressive symptoms, anxiety and life satisfaction respectively. There was strong interrelationship among emotional symptoms. The findings add to our understanding of psychosocial outcomes experienced over time after severe TBI.